A comprehensive overview of evolutionary relationships and geographic distributions of cownose rays: more valid taxa needing protective measures - Yasmim Trindade C. Cunha; Renata Daldin Leite; Lucas Gabriel Pereira da Silva; Vanessa Paes Cruz; Jorge Luiz S. Nunes; Matheus Marcos Rotundo; Paola Palacios-Barreto; Píndaro Diaz-Jaimes; Ana P. Barbosa Martins; M. Aaron Macneil; Chris G. Mull; José Augusto Pires Bitencourt; et al. (Reviews in Fish Biology and Fisheries, 2026)
Rays of the family Rhinopteridae Jordan & Evermann, 1896 are highly migratory and widely distributed in warm tropical and temperate waters. Along the Brazilian coast, the presence of two species has been recorded: Rhinoptera bonasus Mitchill, 1815 and Rhinoptera brasiliensis Müller, 1836. These stingrays are commonly caught as bycatch in trawl fisheries, however, the two species lack distinctive external morphological features that allow for reliable differentiation—species identification is primarily based on the shape and arrangement of teeth in the buccal plates. This study aimed to investigate the evolutionary history of the genus Rhinoptera and to explore which evolutionary drivers, such as biogeographic events or behavioral traits, have influenced its diversification. To achieve this, we analyzed both mitochondrial and nuclear genetic markers, focusing on the species occurring along the Brazilian coast. Specimens of both species were collected across various locations in Brazil, and additional sequences from other Rhinoptera species were obtained from GenBank. Our results reveal the presence of multiple cryptic species within Rhinoptera , particularly within R. bonasus , and likely in Rhinoptera steindachneri Evermann & Jenkins, 1891 and Rhinoptera javanica Müller & Henle, 1841. Notably, R. bonasus does not occur in Brazilian waters nor in parts of the Caribbean where a distinct cryptic sister lineage was identified. Based on our findings, we propose the resurrection of Rhinoptera lalandii Müller & Henle, 1841 as the species representing the lineage found along the Brazilian coast and the Eastern Atlantic Ocean. We suggest that philopatric behavior may represent one of several factors potentially influencing diversification within Rhinopteridae, although this hypothesis requires direct behavioral and population level validation. These findings highlight the urgent need for a comprehensive taxonomic revision of the family, as well as a reassessment of current conservation strategies to better reflect the hidden diversity within this group of species. Graphical abstract

Global Analysis of Shallow Underwater Fish Observation Research: 70 Years of Progress, Persistent Geographic Biases and a Path Forward - Angus John van Wyk; Rick D. Stuart‐Smith; Jordan S. Goetze; Eva Maire; Elodie Heyns‐Veale; Kaylee Smit; Tim J. Langlois; M. Aaron MacNeil; Alejandro Pérez‐Matus; Amanda T. Lombard; Ana Carolina; Christy Semmens; et al. (Fish and Fisheries, 2026)
Marine ecosystems are increasingly threatened by overfishing, pollution, coastal development and climate change, underscoring the need for long‐term, representative information on key fish populations and habitats to inform management and policy. Underwater fish observation (UFObs) techniques, such as Underwater Visual Census (UVC), stereo‐Baited Remote Underwater Video (stereo‐BRUV) and Remotely Operated Vehicles (ROVs), play a key role in sustaining long‐term data collection. Despite technological advancements, gaps persist in understanding research focus, geographic distribution and methodological biases inherent in these methods. We conducted a scientometric analysis of 1443 peer‐reviewed publications (1953–2023), employing natural language processing and network analysis to map the research landscape. We identified 15 knowledge clusters, including marine protected areas, apex predator conservation and reef ecosystems. Our findings reveal increasing use of BRUVS and ROVs in studies of marine protected areas and subsea infrastructure, while UVC remains prevalent in shallow coral reef research. Geographic representation is skewed, with the field dominated by researchers based in Australia and the United States, and underrepresented in Africa and Southeast Asia. This imbalance highlights the need for more inclusive, globally coordinated monitoring and reporting. Our results underscore the urgency of standardising protocols within each observation method and developing interoperable reporting frameworks across techniques to maximise data comparability and foster international collaboration. Addressing these challenges will strengthen the field's capacity to inform global conservation strategies and support sustainable fisheries management.

Development of a tissue-engineered skin model with epidermal, dermal and hypodermal components - V. L. Workman; A-V. Giblin; N. H. Green; S. MacNeil; V. Hearnden (In vitro models, 2023)
Tissue-engineered models of skin have evolved over the past 50 years, have successfully been translated to clinical use and continue to be improved using new technologies. However, very few of these constructs incorporate a hypodermal component. The hypodermis is critical to skin homeostasis, skin function and many skin diseases, but our understanding of the hypodermis is limited in comparison to our knowledge of the epidermis and dermis, in part due to a lack of suitable in vitro models. The purpose of this study was to develop and characterise a tissue-engineered model of skin consisting of epidermal, dermal and hypodermal layers, namely a trilayer skin model. Models were produced by culturing human keratinocytes and fibroblasts on decellularised human dermis in combination with explanted human adipose tissue. Bilayer models of skin, comprising of an epidermis and dermis, had a thicker epidermal component compared to trilayer models but exhibited similar cytokeratin expression patterns (AE1/AE3 and cytokeratin 14). Addition of adipose tissue improved the appearance of the dermal-epidermal junction, increased the number of rete ridge-like features and cells maintained similar levels of proliferation (Ki-67) compared to native tissues over 28 days in culture. This technique enabled us to create a physiologically relevant model of human skin with representative morphology across the hypodermis, dermis and epidermis. This model maintained native extracellular matrix architecture, contained a heterogeneous population of cells and has the potential to be applied to a range of different applications where research questions require the inclusion of a hypodermis.

Managing fisheries for maximum nutrient yield - James P.W. Robinson; Kirsty L. Nash; Julia L. Blanchard; Nis S. Jacobsen; Eva Maire; Nicholas A.J. Graham; M. Aaron MacNeil; Jessica Zamborain‐Mason; Edward H. Allison; Christina C. Hicks (Fish and Fisheries, 2022)
Wild‐caught fish are a bioavailable source of nutritious food that, if managed strategically, could enhance diet quality for billions of people. However, optimising nutrient production from the sea has not been a priority, hindering development of nutrition‐sensitive policies. With fisheries management increasingly effective at rebuilding stocks and regulating sustainable fishing, we can now begin to integrate nutritional outcomes within existing management frameworks. Here, we develop a conceptual foundation for managing fisheries for multispecies Maximum Nutrient Yield (mMNY). We empirically test our approach using size‐based models of North Sea and Baltic Sea fisheries and show that mMNY is predicted by the relative contribution of nutritious species to total catch and their vulnerability to fishing, leading to trade‐offs between catch and specific nutrients. Simulated nutrient yield curves suggest that vitamin D, which is deficient in Northern European diets, was underfished at fishing levels that returned maximum catch weights. Analysis of global catch data shows there is scope for nutrient yields from most of the world's marine fisheries to be enhanced through nutrient‐sensitive fisheries management. With nutrient composition data now widely available, we expect our mMNY framework to motivate development of nutrient‐based reference points in specific contexts, such as data‐limited fisheries. Managing for mMNY alongside policies that promote access to fish could help close nutrient gaps for coastal populations, maximising the contribution of wild‐caught fish to global food and nutrition security.

Assessing accuracy of genotype imputation in the Afrikaner and Brahman cattle breeds of South Africa - S. Mdyogolo; M. D. MacNeil; F. W. C. Neser; M. M. Scholtz; M. L. Makgahlela (Tropical Animal Health and Production, 2022)

Advancing Research for the Management of Long-Lived Species: A Case Study on the Greenland Shark - Jena E. Edwards; Elizabeth Hiltz; Franziska Broell; Peter G. Bushnell; Steven E. Campana; Jørgen S. Christiansen; Brynn M. Devine; Jeffrey J. Gallant; Kevin J. Hedges; M. Aaron MacNeil; Bailey C. McMeans; Julius Nielsen; et al. (Frontiers in Marine Science, 2019)

Chemical and microbial characteristics of municipal drinking water supply systems in the Canadian Arctic - Kiley Daley; Lisbeth Truelstrup Hansen; Rob C. Jamieson; Jenny L. Hayward; Greg S. Piorkowski; Wendy Krkosek; Graham A. Gagnon; Heather Castleden; Kristen MacNeil; Joanna Poltarowicz; Emmalina Corriveau; Amy Jackson; et al. (Environmental Science and Pollution Research, 2018)

Mesopredator trophodynamics on thermally stressed coral reefs - Tessa N. Hempson; Nicholas A. J. Graham; M. Aaron MacNeil; Andrew S. Hoey; Glenn R. Almany (Coral Reefs, 2018)

An appraisal of a biocontamination assessment method for freshwater macroinvertebrate assemblages; a practical way to measure a significant biological pressure? - Calum MacNeil; Mark Briffa; Rob S. E. W. Leuven; Fiona R. Gell; Richard Selman (Hydrobiologia, 2010)

Detection heterogeneity in underwater visual‐census data - M. A. MacNeil; N. A. J. Graham; M. J. Conroy; C. J. Fonnesbeck; N. V. C. Polunin; S. P. Rushton; P. Chabanet; T. R. McClanahan (Journal of Fish Biology, 2008)
This study shows how capture–mark–recapture (CMR) models can provide robust estimates of detection heterogeneity (sources of bias) in underwater visual‐census data. Detection biases among observers and fish family groups were consistent between fished and unfished reef sites in Kenya, even when the overall level of detection declined between locations. Species characteristics were the greatest source of detection heterogeneity and large, highly mobile species were found to have lower probabilities of detection than smaller, site‐attached species. Fish family and functional‐group detectability were also found to be lower at fished locations, probably due to differences in local abundance. Because robust CMR models deal explicitly with sampling where not all species are detected, their use is encouraged for studies addressing reef‐fish community dynamics.